Feasibility of a reproductive system booklet based on an inventory of postpartum medicinal plants - Luviana Putri; Ruqiah Ganda Putri Panjaitan; Titin Titin (Biosfer: Jurnal Pendidikan Biologi, 2026)
Biology learning encompasses complex material, thereby requiring engaging instructional media to enhance students’ understanding. The selection of interesting learning media can increase students’ interest and motivation in the classroom learning process. This study aims to determine the feasibility of a booklet as a learning medium for the reproductive system topic, based on the results of an inventory of traditional postpartum medicinal plants in Teluk Batang Selatan Village, Kayong Utara Regency, West Kalimantan. The research employed a Research and Development (R&D) approach using the Borg and Gall model, which was modified by Sugiyono. The process included five stages: identifying potential and problems, data collection, product design, product validation, and product revision. Data analysis was conducted using Aiken’s V validity index and the Intraclass Correlation Coefficient (ICC) reliability test. The analysis results showed that the average Aiken’s V validity value was 0.94, categorized as very valid, covering the aspects of format (0.91), content (0.97), and language (0.93). The reliability test produced an ICC value of 0.727, categorized as moderate. Based on these results, the developed reproductive system booklet was declared valid, reliable, and feasible for use as a learning medium that integrates scientific concepts with the local wisdom values of the community.